“Wow, it’s nothing like I thought!”: The importance of experience in the early stages of the dissertation process - Dana Dudzinska-Przesmitzki; Sandy Bell (Adult Education Research Conference, 2009)
The use of deliberate practice, communities of practice, and concept mapping can enable doctoral students to make informed decisions in the early stages of the dissertation process. These strategies are particularly effective for students who have limited experience in the research domain of interest.